Enhancement of removal heavy metal using phytoremediation by pistia stratiotes sp. from synthetic wastewater - Teah, Kai Hoong (2014)
In today's modern or developing country, concept of phytoremediation is still the economic way in treating industrial wastewater. Heavy metals such as iron and chromium that contaminated in industrial wastewater can cause serious health problem to living organism. The objective of this research was to perform the removal efficiency of iron and chromium from the synthetic wastewater. The synthetic wastewater was made by following the standards of industrial wastewater to make sure it acts like the genuine industrial wastewater. The aim of the study was to determine the removal efficiency of iron and chromium as the quantities of plant were increased and to study the effect of pH change in constructed wetland. The wetland plant used for the research was water lettuce (pistia stratiotes). For analysis, atomic absorption spectroscopy was used to determine the concentration of iron and chromium. The research was conducted for seven days. Each parameter with varying quantity of plants and pH were carried out in three containers including control. The control container setup with no water lettuce (pistia stratiotes) was to compare the effectiveness. The results for varying quantity of plant for iron removal were 15 plants achieved highest removal efficiency (98.97%), 10 plants (81.23%) and the control (32.33%). For effect of pH experiment for iron removal, the highest removal efficiency achievement was pH 7 (98.97%), pH 4 (45.45%) and pH 10 (37.14%).The results for varying quantity of plant for chromium removal were 15 plants achieved highest removal efficiency (47.95%), 10 plants (35.45%) and the control (19.08%). For effect of pH experiment for iron removal, the highest removal efficiency achievement was pH 7 (47.95%), pH 4 (32.89%) and pH 10 (31.97%). The removal of iron was more effective than chromium. As a conclusion, water lettuce (pistia stratiotes) shows a good result in removing of iron and chromium in wastewater.